Pemberdayaan Masyarakat Terhadap Pendapatan Hasil Nelayan di Pulau Siompu Dalam Memenuhi Kebutuhan Ekonomi - Wa Nur Fida (Indonesian Journal of Education and Social Sciences, 2022)
During the Covid-19 pandemic, the world and Indonesian economies experienced a slowdown and employment became one of the most important factors to lay off some of them because they reduced spending in an income or income crisis at each company. It looks very different from the influence faced when the emergence of the covid-19 virus. Due to the condition of the position of the level of soil fertility that is less likely for them to be able to produce or achieve the needs of economic life to meet the life and position of the world or Indonesia, which is in lockdown, they must be prepared to face life problems that allow them to live. they have to be forced to look for work within their environment, namely by going to sea or getting calls to work, building houses and so on. This study aims to understand the empowerment of coastal communities towards problems their lives from fishing on the island of Siompu in meeting economic needs during the pandemic. The purpose of the study was to determine the empowerment of coastal communities on the income of fishermen on Siompu Island in meeting economic needs during the pandemic. The research method used is qualitative with the type of research is a case study.